2017
DOI: 10.1186/s13568-017-0448-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Arctic microorganisms decomposing bioplastics

Abstract: The increasing amount of plastic waste causes significant environmental pollution. In this study, screening of Arctic microorganisms which are able to degrade bioplastics was performed. In total, 313 microorganisms were isolated from 52 soil samples from the Arctic region (Spitsbergen). Among the isolated microorganisms, 121 (38.66%) showed biodegradation activity. The ability of clear zone formation on emulsified poly(butylene succinate-co-adipate) (PBSA) was observed for 116 microorganisms (95.87%), on poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 24 publications
0
49
0
2
Order By: Relevance
“…were found to have the highest degradation ability. The study further reported Colonostachys roseas as effi cient degrader causing 100% deterioration of starch fi lms within 16 days and 52.91% degradation of PCL fi lm within 30 days at 28˚C [5].…”
Section: Non-biological Degradationmentioning
confidence: 74%
See 3 more Smart Citations
“…were found to have the highest degradation ability. The study further reported Colonostachys roseas as effi cient degrader causing 100% deterioration of starch fi lms within 16 days and 52.91% degradation of PCL fi lm within 30 days at 28˚C [5].…”
Section: Non-biological Degradationmentioning
confidence: 74%
“…This time period allowed polymeric materials to step into every domain of human life [4]. A global estimate suggested plastics production up to three hundred and eleven million tons in 2014 [3,5] and reached up to three hundred and thirty fi ve million tons by 2015 which clearly depicts its enormously rapid production which will become twice in the next two decades whereas will reach nearly four-folds by 2050 [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has identified Ideonella sakaiensis 201-F6 as an efficient biodegrader of PET plastics [42]. Additionally, a recent screen of microbial communities in the Arctic showed promise for plastic degradative abilities in Rhodococcus bacterial species and several fungal species [43].…”
Section: Insight and Intervention For Plastics Bioremediationmentioning
confidence: 99%